2017
DOI: 10.1158/0008-5472.can-16-2984
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Derived miR-25-3p and miR-92a-3p Stimulate Liposarcoma Progression

Abstract: Despite the development of combined modality treatments against liposarcoma (LPS) in recent years, a significant proportion of patients respond only modestly to such approaches, possibly contributing to local or distant recurrence. Early detection of recurrent or metastatic disease could improve patient prognosis by triggering earlier clinical intervention. However, useful biomarkers for such purposes are lacking. Using both patient plasma samples and cell lines, we demonstrate here that miR-25–3p and miR-92a-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 38 publications
4
116
0
Order By: Relevance
“…In recent years, exosomes have been subject of increasing interest in the diagnosis and prognosis of tumors (Alegre et al, 2016; Melo et al, 2015). These small vesicles also exert their biological function to deliver kinds of targeted drugs, such as miRNAs and small interfering RNAs (Casadei et al, 2017; H. Zhang et al, 2017; Y. Zhang et al, 2014). Lately, the exploration of miRNAs and their exosomes suggest a potential role of these regulatory factors in discovering the metastatic potential of cancer cells and mediating cancer‐host communication.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, exosomes have been subject of increasing interest in the diagnosis and prognosis of tumors (Alegre et al, 2016; Melo et al, 2015). These small vesicles also exert their biological function to deliver kinds of targeted drugs, such as miRNAs and small interfering RNAs (Casadei et al, 2017; H. Zhang et al, 2017; Y. Zhang et al, 2014). Lately, the exploration of miRNAs and their exosomes suggest a potential role of these regulatory factors in discovering the metastatic potential of cancer cells and mediating cancer‐host communication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that mature miRNAs with GU-rich sequences also contribute to immune stimulation by serving as physiological ligands for murine TLR7 and human TLR8 (15). For example, miR-21, miR-29a, miR-25-3p, and miR-92a-3p, all harboring GU-rich sequences, have been shown to interact with murine TLR7 and human TLR8 to activate the secretion of proinflammatory cytokines in macrophages (15)(16)(17). Consistent with this, Lehmann et al (18) found that another GU-enriched miRNA, let-7b, acts as a potent activator of TLR7 signaling in neurons, which induces neurodegeneration.…”
Section: Significancementioning
confidence: 99%
“…Oncotarget s470 www.impactjournals.com/oncotarget immune-modulation, angiogenesis, pathogenesis and progression of cancers [7][8][9][10]. Dysregulated circulatory miRNAs have been served as biomarkers for diagnosis, prognosis and prediction in hematopoietic neoplasias [11].…”
Section: Research Papermentioning
confidence: 99%